2013
DOI: 10.1007/s00348-013-1609-0
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of the flow inside the left ventricle of the human heart

Abstract: Exp Fluids (2013) 54(1):1-9 The final publication is available at Springer via http://dx.doi.org/10.1007/s00348-013-1609-0 1 The laboratory models of the human heart left ventricle developed in the last decades gave a valuable contribution to the comprehension of the role of the fluid dynamics in the cardiac function and to support the interpretation of the data obtained in vivo. Nevertheless, some questions are still open and new ones stem from the continuous improvements in the diagnostic imaging techniques.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 43 publications
4
23
0
Order By: Relevance
“…The current flow solver has been successfully applied to cardiac flows in a number of previous studies (8,(37)(38)(39)(47)(48)(49) and has been shown to generate flow features that are inline with in vivo observations (38). A recent validation study (46) for a model ventricle (15) with the same procedure also confirmed that our computational modeling procedure does produce the key features of the velocity and vorticity fields observed in ventricular flows. These previous simulations also provide guidance on the resolution required to model these flows.…”
Section: Methodssupporting
confidence: 59%
See 1 more Smart Citation
“…The current flow solver has been successfully applied to cardiac flows in a number of previous studies (8,(37)(38)(39)(47)(48)(49) and has been shown to generate flow features that are inline with in vivo observations (38). A recent validation study (46) for a model ventricle (15) with the same procedure also confirmed that our computational modeling procedure does produce the key features of the velocity and vorticity fields observed in ventricular flows. These previous simulations also provide guidance on the resolution required to model these flows.…”
Section: Methodssupporting
confidence: 59%
“…Healthy LVs generate vortexes that are by now well characterized (13,15,37), and the flow and dissipation induced by ventricular vortexes are expected to play a key role in modulating the conditions for thrombogenesis in infarcted ventricles. In the present study, 3D vortical structures are identified by the well-established Q-criterion (20).…”
Section: Methodsmentioning
confidence: 99%
“…The process repeats during the A-wave, with a new injection of momentum that further strengthens the large-scale vortex. This recirculation lasts for a large fraction of the cycle (approximately 50 %), and it is very beneficial for the haemodynamics since it constantly sweeps the endocardium and prevents the formation of stagnant flow regions (Fortini et al 2013). When the systole starts, the flow leaves the ventricle from both the aortic and the mitral channel.…”
Section: Flow Induced By Natural and Prosthetic Mitral Valvesmentioning
confidence: 99%
“…This method has already been used in several studies (e.g. Cenedese et al 2005;Fortini et al 2013); details can be found in Miozzi et al (2008).…”
Section: Figmentioning
confidence: 99%